'Managing scarcity'– a qualitative study on volunteer-based healthcare for chronically ill, uninsured migrants in Berlin, Germany. Issue 3 (23rd March 2019) - Linke, Charlotte; Heintze, Christoph; Holzinger, Felix
Abstract : Objectives: In Germany, healthcare for people lacking legal residency status and European Union citizens without health insurance is often provided by non-governmental organisations. Scientific studies assessing the situation of the patients with chronic diseases in this context are scarce. We aimed to characterise medical care for chronically ill migrants without health insurance and outline its possibilities and limitations from the treating physicians' perspective. Design: Qualitative semi-structured interviews; qualitative content analysis. Setting: Organisations and facilities providing healthcare for uninsured migrants: free clinics, medical practices and public health services. Participants: 14 physicians working regularly in healthcare for uninsured migrants. Results: Delayed contact to the healthcare system was frequently addressed in the interviews. Care was described as constrained by a scarcity of resources that often impedes adequate treatment for many conditions, most pronounced in the case of oncological diseases or chronic viral infections (HIV, hepatitis). For other chronic conditions such as cardiovascular diseases or diabetes, some diagnostics and basic medications were described as partially available, while management of complications or rehabilitative measures are frequently unfeasible. For the patients with mental health problems, attainability of psychotherapeutic treatment is reported as severely limited. Care is predominantly described as fragmented with limitations to information flow and continuity. Which level of care a patient receives appears to depend markedly on the respective non-governmental organisation and the individual commitment, subjective decisions and personal connections of the treating physician. Conclusions: Restrictions in medical care for uninsured migrants have even more impact on chronically ill patients. Volunteer-based care often constitutes an inadequate compensation for regular access to the healthcare system, as it is strongly influenced by the limitation of its resources and its arbitrariness.